Emotional and psychological safety in the context of digital transformation in healthcare: a mixed-method strategic foresight study - Silke Kuske; Carmen Vondeberg; Peter Minartz; Mara Vöcking; Laura Obert; Bernhard Hemming; Christian Bleck; Matti Znotka; Claudia Ose; Peter Heistermann; Jutta Schmitz-Kießler; Anne Karrenbrock; et al. (BMJ Health & Care Informatics, 2024)
Background Perceived safety has received attention in the digital transformation of healthcare. However, the impact of perceived safety on the future of digital transformation has not been fully elucidated.Aim To investigate perceived safety in the context of the digital transformation of healthcare while considering relevant needs, influencing factors and impacts, including crisis events, to provide recommendations for action based on a participatory, multiperspective, strategic 5-year foresight viewpoint.Methods A strategic foresight study is conducted via a participatory mixed-methods design to understand the present related factors that are likely to be relevant to future developments in the digital transformation of healthcare.Results We observed that feeling safe plays a complex role in the digital transformation of healthcare. How perceived safety is considered has and will continue to impact the individual, organisational and system levels. Regarding a potential crisis event, controversial consequences have been observed. At its core, digital (health) literacy related to equity of access and human support is one of the crucial aspects in the context of perceived safety related to the successful implementation of digital technologies in healthcare.Conclusions The scenarios showed that a continuation of the current situation over the next 5 years may result in partly desirable and partly undesirable outcomes. Concrete key factors should be used in practice to support both education and healthcare quality development and research. The essence of the scenarios should serve as a starting point for research agenda setting and political decision-making in the future. However, additional research is needed to quantify the correlations among the relevant factors.